2007
DOI: 10.1590/s1413-70542007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do impacto da fragmentação de florestas nativas sobre a mesofauna edáfica na região de Dourados-MS

Abstract: RESUMOEste trabalho, objetivou-se avaliar o impacto da fragmentação sobre a dinâmica populacional de indivíduos da mesofauna edáfica em três fragmentos de florestas nativas na região de Dourados, MS, sendo dois deles localizados em área indígena (Jaguapiru e Bororó) e o terceiro em outra área não indígena (fazenda Azulão). Para avaliar o impacto da fragmentação, foi avaliado o número de Acari Oribatida e Gamasida e insetos Collembola nas três áreas de estudo, utilizando o funil de Berlesse modificado. Observou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
4
Order By: Relevance
“…For example, Silveira Neto, Monteiro, Zucchi, and Moraes (1995) observed a 35.1% reduction in edaphic fauna in forest fragments over 25 years, and Brown and Hutching (1997) observed a decrease in butterfly populations. Furthermore, Gomes et al (2006) observed a decrease in populations of the arthropod order Collembola in forest fragments. In addition to the reduction in population richness, factors such as the loss of genetic variability could also be considered aggravating in terms of the ecological functionality of a fragment.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Silveira Neto, Monteiro, Zucchi, and Moraes (1995) observed a 35.1% reduction in edaphic fauna in forest fragments over 25 years, and Brown and Hutching (1997) observed a decrease in butterfly populations. Furthermore, Gomes et al (2006) observed a decrease in populations of the arthropod order Collembola in forest fragments. In addition to the reduction in population richness, factors such as the loss of genetic variability could also be considered aggravating in terms of the ecological functionality of a fragment.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown a pattern of increase of these variables as a function of successional advancement or environmental preservation as compared with anthropic lands (Tews et al, 2004;Moço et al, 2005;Gomes et al, 2007;Mussury et al, 2008;Machado et al, 2015). These authors concluded that the structural complexity of the vegetation in terms of diversity, led to higher deposition and better quality of litter, providing more favorable conditions of food resources, shelter and reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies that provide information on the Cerrado soil fauna address the way in which the fauna diversity responds to changes depending on the land use (Gomes et al, 2007;Mussury et al, 2008), since these invertebrates are sensitive to the changes generated by the creation of agroecosystems (Decaens et al, 2004). On the other hand, few studies have evaluated the fauna behavior in soils under preserved environments (Pereira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Os grupos com maior poder de dispersão e ampla representatividade funcional, como Coleoptera e Hymenoptera, foram capazes de chegar a capões mais distantes, enquanto grupos com baixa capacidade de dispersão, mas importantes decompositores, porém, com abundâncias representativas em fauna de solo (goMes et al 2007;illig et al 2010), como Collembola, Acari e Psocoptera, foram poucos frequentes (0,68%; 1,72% e 6,55%, respectivamente). (Frizon 2007).…”
Section: Resultsunclassified